LAMINAR FORCED CONVECTION IN HORIZONTAL CHANNEL WITH HEAT GENERATION PLATES COOLED BY WATER - Silva, M. C. da; Novelli, A. D. P. (Revista de Engenharia Térmica, 2016)
This paper describes the study of the behavior of two-dimensional and parallel horizontal flat plates with uniform internal heat generation subjected to laminar forced convection of water. The governing equations are solved numerically using the finite volume technique with Power-Law interpolating scheme and the SIMPLE algorithm. After the simulations the temperature and velocity fields were obtained for various plates spacing and fluid inlet velocities, as well as the Nusselt number values.